Aplikasi Warehouse Inventory Picking Order pada PT. XYZ Menggunakan Symbiotic Organism Search Algorithm - Adelyn Thungriallu; Andreas Handojo; Tanti Octavia (Jurnal Infra, 2021)
Warehouse Inventory Picking Order is the process of taking or placing goods in the warehouse according to the demand list. This is an important process in a company, for example PT. XYZ, because it involves operational costs and can affect the customer satisfaction. Efficiency is needed, especially in the speed and accuracy of picking up or placing products in the warehouse. If the picking order process is efficient, the operational costs and time required will be more efficient too.Unfortunately, this process is often done manually and becomes inefficient due to long and repetitive processes. To answer this problem, a web-based application was designed to determine the route for picking and placing products to minimize the travel distance by using the Discrete Symbiotic Organism Search Algorithm (SOS Algorithm) for discrete data. The final result is that the routing problem can be solved using SOS Algorithm for discrete data with an average distance reduction rate of 38.49% for 25 data.